The Status of the Man in the Nature – the Peculiar Animal - Kieliszek, Zdzisław (Studia Warmińskie, 2011)
The question: who is the man? seems to be the very important philosophical problem. This question focuses many different problems of the philosophy. Recently we have another form of this question: is the man only an animal? The development and results of the biology lead us to the statement – the man is the only one of many elements of the nature, wholly connected with the world. The analysis of the human way of being presents us, that the man is really the part of the nature, but he has the special status in the world. On the one hand he has many features with dead and living nature, especially with the apes. On the other hand the man has the certain attributes and abilities, which have no equivalent in the world of plants and animals. We can say the man belongs to the nature and he steps over it. He is a very peculiar species because he can control his animal nature.